Publish and cherish - Omer, Spahic (IIUM, 2019)
In the academic world, or academia, one frequently hears dispiriting comments to the effect that since not many people read academic research papers, articles and books, most of them should not be embarked on and produced in the first place. It is a waste of time, energy and resources. As a remedy, some suggest that standards be lowered somewhat, and others that teaching and, possibly, community service only be made universities’ raison d’etre. Research and publication should be optional. However, this is a cliché. Needless to say that many academics use that as an excuse to paper over their serious academic shortcomings and underperformance. Universities as educational and research institutions of the highest level are places where knowledge is as much used and consumed, as discovered and produced. It is principally there that the boundaries of knowledge and innovation are expanded, and that new horizons are opened up. It is right there, additionally, that curiosity and abstract intellectualism should be cultivated, sometimes for their own sakes, irrespective of how they may be perceived by others, including students and prospective employers.